Experiences of registered midwives performing termination of pregnancy at Polokwane / Mankweng Hospital Complex in Limpopo Province - Gwangwa, Tshwene Josephine (University of Limpopo, 2014)
Legalising Termination of Pregnancy (TOP) in South Africa has given women the choice to decide to terminate an unwanted pregnancy. The implementation of the Choice on Termination of Pregnancy (CTOP) Act No. 92 of 1996 which was promulgated in 1997 engendered many challenges for the registered midwives performing TOP. A qualitative phenomenological study was conducted to explore and describe the experiences of registered midwives performing TOP at Polokwane / Mankweng Hospital Complex, which is one of the public hospitals in Limpopo Province. Registered midwives with 12 months or more experience in the TOP clinics participated in this study. Interviews were conducted with the participants. The audiotaped interviews and observational notes were transcribed and coded using Tesch’s qualitative and systematic approach of analysing textual data. The major themes that emerged from the data analysis include lack of resources, emotional and psychological trauma, lack of support, religious and cultural beliefs, blaming and coping mechanisms. Several sub-themes were identified that reflected the themes in greater detail. These were shortage of human and material resources, stress and frustration of midwives, rejection and labelling of midwives performing TOP, conscientious objection, cultural beliefs, lack of support by colleagues and management, failure by the community to use contraceptives, self-blaming, debriefing to assist registered midwives and self-acceptance. Guidelines based on contextualisation of these themes and sub-themes to improve identified challenges included retention of personnel through recognition and incentives, increase budgeting for essential equipment, planned debriefing sessions, promotion of positive attitudes by colleagues and intense training on reproductive health, including TOP.
Thesis (MPH.) -- University of Limpopo, 2014
Keywords: Termination of pregnancy; Registered midwives; 618.2; Midwives -- South Africa -- Limpopo; Abortion -- South Africa -- Limpopo; Abortion services -- South Africa -- Limpopo